Frequency of Pregnancy Linked Acute Kidney Damage a Single-Center Study - Surraya Israr, Parveen Shafi, Kiran Ikram, Romaisa Zeb, Lubna Tahir, Sumaira Yasmin (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acute kidney damage in pregnancy is an unusual but serious complication of pregnancy. Among developed countries, PR-AKI has decreased from 4% to 4.4%. PR-AKI is quite widespread in underdeveloped countries. In impoverished nations like Pakistan, the actual incidence of obstetrics-related AKI and its change are unknown. This research aims to measure acute kidney damage during pregnancy in our setting. Objective: Acute kidney injury (AKI) caused by pregnancy is often documented. To diagnose pregnancy- related AKI. Methods: the study was conducted in the Department of Obstetrics and Gynecology Bacha khan medical college sawabi from 24 June to 24 June 2020. Eighty-seven samples size were included in the study using sequential sample after the areas and (OPD) through A single center study design. The serum creatinine levels were used to diagnose acute renal damage during pregnancy. SPSS version 2.2 for the purpose of data analysis. A mean and standard deviation were determined. for continuous variables such as gestational period, age, and birth weight. Variables like AKI had their frequencies and percentages assessed. The results were then broken down by factors like gestational age and length of pregnancy to determine whether there were any impact modifiers. The significance level was set at P 0.05. Results: The average age of the investigated population was 24 years 2. years old. The pregnancy lasted an average of 3 months, with a standard deviation of 5.112. Acute kidney damage (AKI) was found in only 4% of the 87 individuals investigated, compared to 93% of the patients without AKI. Conclusion: Pregnancy-related acute renal damage was shown to be 7 percent common in our setting, according to the results of our research. Keywords: Creatinine Levels, Pregnancy, Acute Kidney Injury